Government Provision of Infant Formula in Egypt - George Kent; Ghada Sayed; Azza Abdul-Fadl (Social Medicine Publication Group, 2017)
Egypt has a long history of providing subsidized food for its people. The policy has been criticized for its high cost to the government and for the way in which sustained provision of food by the government can be disempowering for the people (Ecker, Tan, and Al-Riffai 2014; Ecker et al. 2016); IFPRI 2013). This editorial will examine one distinct component of that program: the provision of subsidized infant formula. As shown in the historical review, the subsidy program was in turmoil in mid-2016, resulting in major changes in the program's management. The critical analysis that follows argues that for the long term, simply improving the delivery of subsidized formula is not enough. It should be recognized that feeding infants with formula can displace breastfeeding, resulting in worse health outcomes for infants and mothers. The use of infant formula should not be encouraged. There are few conditions under which it is medically necessary. Instead of spending so much money on subsidizing formula, Egypt should provide better support for breastfeeding.